Calculation Of Total Wash Under The Bridge Based On Guideline Flow Velocities - Shavkatovich, Rakhimov S Herzod; Soibjon, Botirov is the son of Shokhbos Soibjon; Mukhtar, Shodiyev is the son of Ramshid (Journal of Geography, Regional Planning and Development, 2024)
Many years of study, modeling, and theoretical studies of the working conditions of bridge crossings have made it possible to significantly improve the methods of determining the size of clear spans under large and medium-sized bridges. Prof. The further development of the method, founded by NA Belelyubsky, consisted in calculating the flow rate at which the under-bridge washout stops. The need for velocity calculation arose after observations of the phenomenon of bridge span washes often stopping at average flow velocities rather than domestic velocities.